Asymptotic solutions to the first order differential equation with deviated argument and slowly varying coefficients - Mitropolsky, Y.A.; Matarazzo, G.; Pompei, A.; Samoilenko, V. H. (Нелінійні коливання, 2004)
The object of this paper is to study the problem of constructing an approximate solution to the first order weakly nonlinear ordinary differential equation with deviated argument and slowly varying coefficients. Based on asymptotic techniques in nonlinear mechanics an algorithm for asymptotic integration of the differential equation under consideration is given.